FREKUENSI PEMBERIAN GROW QUICK LB TERHADAP PERTUMBUHAN BIBIT ANGGREK DENDROBIUM PADA STADIA KOMUNITAS POT - SURTINAH SURTINAH; ENNY MUTRYARNY (Jurnal Ilmiah Pertanian)
ABSTRACT This research was held at screen house of Fakultas Pertanian Unilak, this experiment is a kind of research that using 1 factor of 2 treatments which the Grow Quick LB fertilizer giving 3 times a day and the Grow Quick LB fertilizer giving 6 times a day. The growth of Anggrek Dendrobium seedling that observed are the length of bud, the length of bud’s leaves, the width of bud’s leaves, and the number of bud’a leaves. The abtaining data was analyze which used t – Test. The result of the 3 times giving Grow Quick LB fertilizer treatment a day is the best growing of Anggrek Dendrobium.